2019
DOI: 10.1097/bsd.0000000000000786
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Concurrent Validity of PROMIS Physical Function in Anterior Cervical Discectomy and Fusion

Abstract: Study Design: This study was a retrospective cohort analysis. Objectives: This study aims to evaluate the concurrent validity of Patient-Reported Outcomes Measurement Information System (PROMIS) Physical Function (PF) domain as compared with legacy measures of patient-reported outcomes (PROs) among patients undergoing anterior cervical discectomy and fusion (ACDF). Summary of Background Data: As PROMIS becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…12 PROMIS PF is most commonly used in spine surgery and is beneficial for understanding range of motion, mobility, and postoperative coordination. 20 PROMIS PF has been increasingly used to psychometrically evaluate pre and postoperative outcomes of spinal surgery. 11,27 Multiple investigations of multilevel ACDFs have shown that PROMIS PF correlates with NDI and SF-12 during preoperative and short-term postoperative time points.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…12 PROMIS PF is most commonly used in spine surgery and is beneficial for understanding range of motion, mobility, and postoperative coordination. 20 PROMIS PF has been increasingly used to psychometrically evaluate pre and postoperative outcomes of spinal surgery. 11,27 Multiple investigations of multilevel ACDFs have shown that PROMIS PF correlates with NDI and SF-12 during preoperative and short-term postoperative time points.…”
Section: Discussionmentioning
confidence: 99%
“…11,27 Multiple investigations of multilevel ACDFs have shown that PROMIS PF correlates with NDI and SF-12 during preoperative and short-term postoperative time points. 20 One study further highlighted that PROMIS PF can accurately compare patient improvement from preoperative scores out to 1 year postopera- tively. 28 Vaishnav et al 29 found significant associations between NDI and PROMIS PF, as well as between SF-12 PCS and PRO-MIS PF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11][12] The development of the Patient-Reported Outcomes Measurement Information System (PROMIS) physical function (PF) reflects an improvement in many of these shortcomings, and furthermore, is becoming increasingly validated with respect to ACDF procedures. 13,14 An analysis of PROMIS PF scoring is ideal for ACDF procedures because the system allows for a more global health assessment, fewer questions, and without the need to administer different questionnaires for separate anatomical locations (e.g., arm, neck, etc.). These new strengths increase the utility of PROMIS and may reduce clinical burden.…”
Section: Introductionmentioning
confidence: 99%